Anti-IL-6 therapies in central nervous system inflammatory demyelinating diseases - Jiao, Li; Guo, Shougang (Frontiers in Immunology, 2022)
Current treatments for central nervous system (CNS) inflammatory demyelinating diseases (IDDs) include corticosteroids, plasma exchange, intravenous immunoglobulin, and immunosuppressant drugs. However, some patients do not respond well to traditional therapies. In recent years, novel drugs, such as monoclonal antibodies, targeting the complement component C5, CD19 on B cells, and the interleukin-6 (IL-6) receptor, have been used for the treatment of patients with refractory CNS IDDs. Among these, tocilizumab and satralizumab, humanized monoclonal antibodies against the IL-6 receptor, have shown beneficial effects in the treatment of this group of diseases. In this review, we summarize current research progress and prospects relating to anti-IL-6 therapies in CNS IDDs.